Present status and socio-cultural acceptability of traditional bamboo houses: a study in Kerala and Karnataka states of India - P. K. MURALEEDHARAN, V. ANITHA and T. D. SIMON (J. Bamboo and Rattan, Vol. 3, No. 3, pp. 283-296 (2004), 2004)
An attempt is made in this paper to assess the present status, particularly structure, costof construction, long-term economic benefits and socio-cultural acceptability of traditional bamboo houses in Kerala and Karnataka states of India. It also examines the major constraints and policy changes required for the promotion of bamboo houses in the study areas. This study is based on a sample survey conducted among 360 selected households dwelling in bamboo houses. Although bamboos are widely available in the study areas, the housing sector experiences severe shortage of bamboos for construction, as the pulp and paper industry purchases bamboos on a large scale by offering higher prices. In the study areas, bamboo houses are either thatched with grass or leaves or tiled using country tiles. It is reported that about 95 per cent of the dwellers prefer tiled houses because of its durability and low maintenance cost. It is also observed that the economic benefits and sociocultural acceptability of tiled bamboo houses are higher. Poor economic conditions of the dwellers, low availability of bamboos in the construction sector, high prices of bamboo and lack of title deeds of the land are some of the major constraints identified for the promotion of bamboo houses. Italso suggests that bamboo houses in the study areas may become more popular by providing more amenities and better appearance for aesthetic satisfaction